2021
DOI: 10.3389/fimmu.2021.638066
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Tissue Transcriptomic Analysis Leveraging Machine Learning Approaches Identifies New Biomarkers for Rheumatoid Arthritis

Abstract: There is an urgent need to identify biomarkers for diagnosis and disease activity monitoring in rheumatoid arthritis (RA). We leveraged publicly available microarray gene expression data in the NCBI GEO database for whole blood (N=1,885) and synovial (N=284) tissues from RA patients and healthy controls. We developed a robust machine learning feature selection pipeline with validation on five independent datasets culminating in 13 genes: TNFAIP6, S100A8, TNFSF10, DRAM1, LY96, QPCT, KYNU, ENTPD1, CLIC1, ATP6V0E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…An adaptive deep neural network [ 137 ] was able to outperform non-DL methods in predicting DAS28-ESR from demographical and clinical data with an AUC of 0.73 (categorical prediction) and mean standard error of 0.9 (numerical prediction). However, the attempt by Rychkov et al [ 138 ] to predict DAS28 using omics data yielded unsatisfactory results, and their novel RA score showed only a weak ( r = 0.33) correlation with DAS28. The clinical disease activity index (CDAI) [ 139 ] is another scoring system that only uses clinical data and can be calculated more rapidly than DAS28.…”
Section: Artificial Intelligence In Ramentioning
confidence: 99%
See 1 more Smart Citation
“…An adaptive deep neural network [ 137 ] was able to outperform non-DL methods in predicting DAS28-ESR from demographical and clinical data with an AUC of 0.73 (categorical prediction) and mean standard error of 0.9 (numerical prediction). However, the attempt by Rychkov et al [ 138 ] to predict DAS28 using omics data yielded unsatisfactory results, and their novel RA score showed only a weak ( r = 0.33) correlation with DAS28. The clinical disease activity index (CDAI) [ 139 ] is another scoring system that only uses clinical data and can be calculated more rapidly than DAS28.…”
Section: Artificial Intelligence In Ramentioning
confidence: 99%
“…Table 8 summarizes studies implementing ML and DL for monitoring disease course and predicting prognosis [ 79 , 137 , 138 , 140 , 141 , 146 , 147 , 149 , 157 166 ].…”
Section: Artificial Intelligence In Ramentioning
confidence: 99%
“…Lymphocyte antigen 96 (LY96), also known as myeloid differentiation 2 (MD2), is required for the activation of TLR4 by lipopolysaccharide (LPS), which plays an important role in innate immunity and is the first line of defense against microbial infection ( Dou et al, 2013 ). LY96 plays a vital role in inflammation-related and immune-related diseases such as Crohn’s disease ( Yang et al, 2021 ), rheumatoid arthritis ( Rychkov et al, 2021 ), and inflammatory diabetic cardiomyopathy ( Wang et al, 2020a ). Recently, several studies revealed that LY96 was tightly correlated with tumor initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…By bioinformatics analysis, FN1, VEGFA, HGF, SERPINA1, MMP9, PPBP, CD44, FPR2, IGF1, and ITGAM were recognized as the hub genes related to synovial macrophages in RA [ 20 ]. Furthermore, TNFAIP6/TSG6 and HSP90AB1/HSP90 were identified as new biomarkers for RA by cross-tissue transcriptomic analysis leveraging machine learning approaches [ 21 ]. However, there are some shortcomings in these findings.…”
Section: Introductionmentioning
confidence: 99%